Perancangan Laporan Keuangan Berbasis Microsoft Excel Di UMKM Ridkah - santi widiawati; vina adriana (LPPM POLITEKNIK LP3I BANDUNG, 2026)
This article aims to design a systematic and automated financial reporting system using Microsoft Excel for Ridkah SMEs. The results of the research presented in this article are a digital accounting application that integrates the Chart of Accounts (COA), General Journal, and Ledger into automatic financial reports based on the SAK EMKM standards. The implementation of the system shows that using this application provides significant efficiency in data processing and produces accurate financial information, thereby supporting better business decision-making for SME owners.